Improving Primary Care Capacity Through Mental Health Training: A Scoping Review - Sutejo Sutejo; Findri Fadlika (GLOBAL HEALTH SCIENCE GROUP, 2026)
Mental health is a significant challenge in primary health care, particularly in lower-middle-income countries that face a shortage of mental health workers. In this situation, training for health workers is an important strategy to increase the capacity of existing resources and optimize the role of health care providers in mental health service delivery. This scoping review aimed to identify the impact of training mental health workers in primary care, particularly in terms of improved screening and early detection, increased utilization of mental health services, and improved clinical outcomes. The scoping review used the Arkey and O'Malley approach. Articles were searched using three databases, such as Medline, ProQuest, and Scopus, published between 2020-2025. Of the 1,475 articles identified, nine articles met the inclusion criteria and proceeded to the analysis stage. Training mental health workers in primary care was shown to improve health workers' knowledge, skills, attitudes, and self-efficacy. The impact of training was also seen in an increase in the number of screenings and early detection of mental disorders, increased utilization of mental health services, and significant improvements in psychotic symptoms, depressive symptoms, anxiety, and social functioning of patients. Training primary care health workers can improve the capacity and quality of mental health services. Appropriate training design, adequate duration, and ongoing evaluation systems are essential to ensure successful intervention and long-term impact on patient health.